Investment Advising: Pay-to-Play, or Capture? - Xanthopoulos , Apostolos (SPOUDAI Journal of Economics and Business, 2019)
In “Theory of Economic Regulation,” Stigler introduces the ideas of demand for, and supply of regulation (Stigler, 1971). Similar to capture in regulation, consultants to institutional investors enhance the benefits of their own firms, create a loss in information ratio to their clients, and reveal capture in their classification schemes, which serve the interests of portfolio managers that demand intermediation. Portfolio managers are modeled as perceptron units with a tactical element and a strategic mandate. The classification schemes of portfolios, supplied by internet platforms of consulting firms, distort the ‘default’ tactical prominence over strategic mandates and reshuffle the reviewed portfolios away from contemporaneous, performance-based rankings. Due to capture, the excess-fee incentive becomes compatible only with inconsistent narratives that the consultants of the firm can deliver to a client. The bifurcation in accountability between client-facing consultants and platform-supporting researchers creates a technology-amplified vacuum perceived by money management firms, which then rush-in to establish advisory capture. In a manner that “defies rational explanation” consulting firms appear cognizant of, but shun the better way to serve their clients (Stigler, 1971:3). In addition to fees, institutional investors stoically bear the loss in risk-adjusted performance, as their responsibility-transfer enables advisory capture. Ultimate realization of the loss due to on-line classifications, combined with conflicting scenarios embedded in classification schemes, may result in systemic-level redemptions that should concern the U.S. and global regulatory authorities. JEL Classification: G11, G18, G23